Membentuk Jiwa Leadership pada Santri Pesantren Modern Saifullah An-Nahdliyah Melalui Kegiatan Outing Class - Dewi Shinta Wulandari Lubis; Soraya Grabiella Dinamika; Yurial Arief Lubis (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service activity aims to provide knowledge about leadership to santri and santriwati in the Saifullah An-Nahdliyah Modern Islamic Boarding School environment through Outing Class activities. A total of 40 people from several grade levels equivalent to SMP / MTs and SMA / MA, consisting of 22 male students, and 18 female students participated in this activity. The method of this community service activity uses the lecture method, direct demonstration, discussion, and question and answer. The lecture method was used to convey general knowledge about leadership. Demonstration is used to provide direct skills regarding understanding, how to form, and types of leadership by utilizing existing games and tools. Discussion and question and answer are used to complete things that have not been accommodated by the two methods above. The obstacle faced is that the students do not have prior knowledge about leadership. The service team provided material on leadership and teamwork, then Outing Class activities were carried out by playing several types of leadership games such as leaking pipe games, rigging games, water tower games, Human Ladder games, and moving bracelets games. The post-test results showed that after participating in the activity the participants' understanding and knowledge of leadership increased, as shown by the N-gain results which were categorized as high (g> 0.7). Benefits that can be obtained by participants